Self-Motivation Analysis of Family Planning Field Officers in Implementing Family Planning Programs at the P2AP2KB Office of North Nias Regency - Purnamasari Nazara; Wisnu Hidayat; Masdalina Pane; Frida Lina Tarigan; Rahmat Aliyakin Dachi (TOUR HEALTH JOURNAL, 2022)
Family planning is an attempt to spacing or planning the number of children and the length of pregnancy using contraceptives. Family planning, namely limiting the number of children in a family where only two children are allowed. Family planning that is allowed is an effort to regulate or restrict births or an effort to prevent pregnancy temporarily based on the agreement of the husband and wife due to certain situations and conditions for the benefit of the family, society, or the state. In implementing the family planning program, it is very necessary to have a major contribution that plays a role in it, namely the Family Planning Field Officer (PLKB), which is the vision of the BKKBN organization, namely the institutionalization of happy and prosperous small family norms and creating quality families. To achieve this is needed as a driving factor for behavior someone, and the driving factor is none other than a need and desire of someone to carry out an activity. If someone wants something, he will be motivated to do certain activities to get what he needs. This is a qualitative research with a descriptive-qualitative approach. This study used a qualitative method design which is a research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The aim is to analyze the Self Motivation of Family Planning Field Officers in Implementing the Family Planning Program (KB) in the P2AP2KB Office of North Nias Regency. This research was conducted by presenting information from 4 sub-districts of in-depth interview data collection techniques, it was concluded that the self-motivation of Family Planning Field Officers in implementing the Family Planning program, a lot of knowledge, especially training sent to the field of PLKB self-motivation is directly related to their performance in implementing the program. family planning, lack of field extension officers in every village, problems and obstacles faced by PLKB, the community is still less interested in becoming family planning acceptors, human resources in family planning services are still lacking, understanding of PLKB related to reporting is not good and cooperation between health facility midwives and village heads not good.